Crystal structure of fac-(acetylacetonato-κ2O,O′)tricarbonyl(benzyldiphenylphosphine-κP)rhenium(I), C27H24O5PRe - Manicum Amanda-Lee; Alexander Orbett; Schutte-Smith Marietjie; Visser Hendrik G.; Roodt Andreas (Zeitschrift für Kristallographie - New Crystal Structures, 2017)
C27H24O5PRe, triclinic, P1̄ (no. 2), a = 9.0305(17) Å, b = 12.084(2) Å, c = 12.403(2) Å, α = 89.688(6)°, β = 70.083(6)°, γ = 76.315(6)°, V = 1232.2(4) Å3, Z = 2, Rgt(F) = 0.0180, wRref(F2) = 0.0432, T = 100(2) K.